Environmental factors that affect the incidence of stunting in under-five children: A literature review - Adi, Sugiono; Krisnana, Ilya; Rahmawati, Praba Diyan; Maghfiroh, Umi (Universitas Airlangga, 2023)
Introduction: Stunting and other health issues affecting children under five result from unhealthy environments. Environmental sanitation by providing sanitary latrines and clean water supplies cannot be divorced from its influence. A review of the literature was conducted to assess how healthy latrines and clean water sources can improve stunting in children under the age of five.Methods: Four databases (Scopus, ProQuest, Science Direct, and Google Scholar) with high and medium-quality standards were used to find the articles for this literature study. The study's quality was judged using Joanna B Institute's criteria. The research is included in the inclusion criteria if it has a critical assessment score of at least 50%. PICOS used as the review's organizing structure.Results: The availability of clean water sources and sanitary latrines significantly impacts stunting. Access to subpar latrines increases the risk of stunting in children under five. Stunting in children under five is influenced considerably by the availability of safe water sources.Keywords: environmental factors; stunting; under-five children